KARAKTERISTIK DAN PREFERENSI WISATAWAN MANCANEGARA SERTA PRIORITAS KEBIJAKAN PEMERINTAH SEBAGAI BAHAN ACUAN PENGEMBANGAN INVESTASI DI BALI - M.Th. Anitawati; Agni Alam Awirya; Rani Setyodewanti (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2012)
As a famous tourist destination, Bali has to keep doing the development and improvement of tourism facilities and infrastructures in order to remain attractive fo tourists. In doing so, it is needed funds from investors. Investment in the tourism sector has to consider government support and needs of tourists. The study used data from 235 foreign tourists (tourists) in Bali and 5 Policy Makers Which Interviewed to determine their perceptions about tourism development in Bali. Factor analysis and AHP show that comport and security are important factors for travelers. Therefore, investement in the hospitality sector still has a good chance . Substantial funds are needed to develop convinient and affordable transportation. Combination of perceptions between tourists and policy makers gives greater opportunity for investors to develop not only coastal tourism but also culture tourism.